The Role of the Family as the Cornerstone of Children’s Education from an Islamic Perspective - Eko Nursalim; Hasan Hasan; Indah Fani Damayanti; Hanifah Tarisa Budiyanti (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This study employs a literature review method. This method involves seeking answers in books and articles. The researcher reviewed numerous books and articles related to the research topic. This article examines the central role of the family in the education of Muslim children. As the first and primary institution in a child’s life, the family exerts a significant influence on the formation of a child’s character, morals, and religious values. This study highlights various educational methods that can be applied within the family, such as modeling, habit formation, guidance, attention, and, under certain conditions, discipline. Parental modeling is the key to shaping a child’s character, while instilling religious values from an early age helps cultivate a strong faith. Comprehensive Islamic religious education, which encompasses creed, morals, and worship, is also a vital component in shaping the personality of Muslim children. Additionally, this article discusses the importance of creating a family environment conducive to a child’s growth and development. In conclusion, the family plays a crucial role in raising a future generation that is of high quality, possesses noble character, and is capable of facing the challenges of the times.